ANALISIS PELAKSANAAN STRATEGI PENGEMBANGAN KOPERASI TIDAK AKTIF DI JAWA TENGAH - Abdul Hakim Pranata Putra; Hardi Warsono (Journal of Public Policy and Management Review, 2016)
This research was compiled in order to know the implementation strategies used Department of cooperatives and UMKM in Central Java and knowing the factors – factors that hampered the development of cooperatives in Central Java. Development of the number of active cooperatives in Central Java as much as 22.674 (81,37%), but was not accompanied by a reduced number of cooperatives is not active in Central Java with the amount of 5.191 (18,62%). This Research is qualitative research typedescriptive with datacollection through interview, observation, and study of the literature. Informants were taken by researchers is the head of Department of cooperatives and UMKM in Central Java, head of cooperative empowerment, head of the cooperative program, the head of the cooperative loan, Head of cooperative training Hall, head of assessment and development of cooperativetraining Hall, KSU Putra Cahaya Implementation of the strategy Department of cooperatives and UMKM of Central Java in developing cooperatives in Central Java in ways that embody the first cooperative sehatdan quality, the two developed a superior product Areas of Central Java which empowered the third competitiveness, embody the human resources Manager of the cooperative that competent, professional apparatus embodying the fourth, dedicated, responsive and excellent service-oriented in empowering cooperatives, in pelaksanaanya there is still the problem that is There are still many communities that do not know what is cooperative, there are still operatives are less healthy and unhealthy, HR administrators a less competent, cooperative and the difficult access to capital loan obtained.